Adoption of the marketing mix in small and medium-sized enterprises: Some suggestions - Hashim, Mohd Khairuddin; Hassan, Romle (UUM Press, 2011)
The marketing concept is relevant and applicable to all types of organizations. Although marketing is important to both large and small and medium-sized enterprises (SMEs), the literature appear to indicate that previous studies on marketing practices and activities have mainly emphasized examining large firms.The review of the literature shows the focus on marketing in the context of SMEs remained limited and neglected.This paper attempts to provide some insights into the relevance and applicability of the marketing mix to SMEs.More precisely, the paper seeks to show how the concept as well as the tools of the marketing mix can be applied in SMEs.